2015
DOI: 10.1021/ic502991p
|View full text |Cite
|
Sign up to set email alerts
|

Open-Shell Lanthanide(II+) or -(III+) Complexes Bearing σ-Silyl and Silylene Ligands: Synthesis, Structure, and Bonding Analysis

Abstract: Complexes featuring lanthanide (Ln)–Si bonds represent a highly neglected research area. Herein, we report a series of open-shell LnII+ and LnIII+ complexes bearing σ-bonded silyl and base-stabilized N-heterocyclic silylene (NHSi) ligands. The reactions of the LnIII+ complexes Cp3Ln (Ln = Tm, Ho, Tb, Gd; Cp = cyclopentadienide) with the 18-crown-6 (18-cr-6)-stabilized 1,4-oligosilanyl dianion [(18-cr-6)KSi(SiMe3)2SiMe2SiMe2Si(SiMe3)2K(18-cr-6)] (1) selectively afford the corresponding metallacyclopentasilane s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
76
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(89 citation statements)
references
References 81 publications
10
76
3
Order By: Relevance
“… 14 , 27 , 29 31 The bond distances of the Eu–Si bonds in 2b (3.2052, 3.2162 Å) and 4b (3.1497 Å) are comparable to that found in Cp* 2 Eu II SiH 3 K(THF) 2 (3.239 Å). 13 For 2c (3.2132 and 3.2444 Å) and 4c (3.1716 Å) the Si–Sm distances are in good agreement with the few published Sm(III)–Si bond lengths (3.133, 3.106, and 3.174 Å) 9 and the known Sm(II)-silylene complexes (3.189 10 and 3.299 11 Å). In general compounds 4a – c with the two bulky tris(trimethylsilyl)silyl groups exhibit the shorter bond lengths compared to the metallacyclopentasilanes 2a – c .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“… 14 , 27 , 29 31 The bond distances of the Eu–Si bonds in 2b (3.2052, 3.2162 Å) and 4b (3.1497 Å) are comparable to that found in Cp* 2 Eu II SiH 3 K(THF) 2 (3.239 Å). 13 For 2c (3.2132 and 3.2444 Å) and 4c (3.1716 Å) the Si–Sm distances are in good agreement with the few published Sm(III)–Si bond lengths (3.133, 3.106, and 3.174 Å) 9 and the known Sm(II)-silylene complexes (3.189 10 and 3.299 11 Å). In general compounds 4a – c with the two bulky tris(trimethylsilyl)silyl groups exhibit the shorter bond lengths compared to the metallacyclopentasilanes 2a – c .…”
Section: Resultssupporting
confidence: 86%
“…The few reported samarium silyl compounds, which have also been characterized by X-ray diffraction analysis, feature Sm with Cp* ligands almost exclusively in oxidation state 3+ 7 9 with the exception of some divalent silylene complexes reported by Evans and co-workers 10 and our group. 11 The reaction of Cp* 2 Yb·(Et 2 O) with (Me 3 Si) 3 SiLi was shown to result in the formation of Cp*YbSi(SiMe 3 ) 3 ·(THF) 2 accompanied by elimination of Cp*Li. 12 Reacting Cp*YbSi(SiMe 3 ) 3 ·(THF) 2 with excess (Me 3 Si) 3 SiLi led to the formation of some 30% of [(Me 3 Si) 3 Si] 2 Yb·(THF) x , which could not be isolated.…”
Section: Introductionmentioning
confidence: 99%
“…An X‐ray diffraction study on single crystals of 1 revealed a uranium–silicon bond length of 3.1637(1) Å (Figure ). While this distance is longer than the sum of the covalent radii of uranium and silicon as tabulated by Pyykkö (2.86 Å) or Alvarez (3.07 Å), bond lengths between f ‐elements and heavy main‐group atoms have often exceeded the sums of the relevant covalent radii, suggesting that these radii may not be the best predictor of main‐group–f element bond length . Compared to its ‘base‐free’ solid‐state structure, the (CpSiMe 3 ) 3 U fragment has reorganized to minimize unfavorable steric interactions: the trimethylsilyl (TMS) groups on the cyclopentadienyl rings of (CpSiMe 3 ) 3 U are oriented away from the fourth ligand, an arrangement that has only been observed previously in some dimeric structures containing bridging ligands .…”
Section: Methodsmentioning
confidence: 94%
“…The 2010 discovery by Roesky and co-workers that amidinate-supported silylenes could be prepared in high yield throughd ehydrochlorinationp athways hasc aused a surge of growth in their research and application; [18,19] these silylenesh ave been bound to metals from nearly every group in the transition-metal series [20] as well as to lanthanides. [21] The growinga pplication of these silylenes is largely due to the ease with which the parent chlorosilylene Si[PhC(NtBu) 2 ]Cl can be derivatizedt of eature substituents such as alkoxy, amino, phosphino, and even alkyl groups, thus accessing an array of silylenes with varying steric and electronic properties. [20,22,23] In 2009, we showed that the uranium(III) complex (CpSi-Me 3 ) 3 Uc ould be employed to generate speciescontaining actinide-group 13 bonds with aluminum(I) and gallium(I).…”
mentioning
confidence: 99%
See 1 more Smart Citation